2018
DOI: 10.1016/j.trf.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

A study in real traffic examining glance behaviour of teenage cyclists when listening to music: Results and ethical considerations

Abstract: Listening to music while cycling impairs cyclists' auditory perception and may decrease their awareness of approaching vehicles. If the impaired auditory perception is not compensated by the cyclist himself or other road users involved, crashes may occur. The first aim of this study was to investigate in real traffic whether teenage cyclists (aged 16-18) compensate for listening to music by increasing their visual performance. Research in real traffic may pose a risk for participants. Although no standard ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Listening to music via earphones did not have significant effects on workload (NASA-RTLX) or the behaviour measures examined here. This is in agreement with other studies on cyclists (Ahlstrom et al 2016;Stelling-Konczak et al 2018) as well as on pedestrians (Hyman et al 2010;. On the top of the list of self-reported behaviour adaptations, as a means to compensate for the loss of auditory information, is increased visual attention (Adell et al 2014;Stelling-Konczak et al 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Listening to music via earphones did not have significant effects on workload (NASA-RTLX) or the behaviour measures examined here. This is in agreement with other studies on cyclists (Ahlstrom et al 2016;Stelling-Konczak et al 2018) as well as on pedestrians (Hyman et al 2010;. On the top of the list of self-reported behaviour adaptations, as a means to compensate for the loss of auditory information, is increased visual attention (Adell et al 2014;Stelling-Konczak et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…On the top of the list of self-reported behaviour adaptations, as a means to compensate for the loss of auditory information, is increased visual attention (Adell et al 2014;Stelling-Konczak et al 2017). Stelling- Konczak et al (2018) found that 21% of the cyclists increased and 57% decreased their visual scanning to the right in intersections, when listening to music. Out of the total amount of intersections, 49% were attended in baseline and 41% in the music condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings concerning visual behaviour of cyclists found in our study and other surveys appear inconsistent with the results of on-road studies. Specifically, the increase in visual behaviour reported by cyclists in survey studies is not found in on-road research in which cyclists' visual behaviour whilst listening to music was similar to the visual behaviour while 'just' cycling (Ahlstrom et al, 2016;Stelling-Kończak et al, 2018). As for talking on the phone, cyclists who engaged in this activity were in the study of Ahlstrom et al found to use visual strategies: they decreased their glances towards traffic-irrelevant targets and shortened glance durations to traffic relevant targets, while maintaining the number of glances.…”
Section: Compensatory Behaviour While Listening To Music and Talking mentioning
confidence: 84%
“…Kircher & Ahlstrom, 2017a;Lemonnier et al, 2015;Robbins & Chapman, 2018;Underwood, Chapman, Brocklehurst, Underwood, & Crundall, 2003;Walker & Brosnan, 2007;Werneke & Vollrath, 2012) and cyclists (e.g. Ahlstrom, Kircher, Thorslund, & Adell, 2015;Frings, Parkin, & Ridley, 2014;Nygårdhs, Ahlström, Ihlström, & Kircher, 2018;Stelling-Konczak et al, 2018;Uetake & Shimoda, 2014). Typically, it is studied what the road user looks at/allocates attention to, depending on various factors.…”
Section: Introductionmentioning
confidence: 99%